Long-term follow up of dorsal root entry zone lesions in brachial plexus avulsion. Issue 6 (June 1994) - Thomas, D G; Kitchen, N D
Abstract : The long-term results of 44 patients who underwent dorsal route entry zone (DREZ) lesioning for pain secondary to brachial plexus avulsion are reported with a mean clinical follow up period of 63 months. The postoperative analgesic effect was judged by the patients as being good (greater than 75% pain reduction), fair (25-75% pain reduction), or poor (0-25% pain reduction). With these criteria 35 patients (77%) had continuing good (30 cases, 68%) or fair (five cases, 11%) pain relief at the time of final follow up. Eight cases (18%) had persisting neurological deficits, although these were generally mild. DREZ thermocoagulation is an effective procedure for relieving deafferentation pain. The analgesic effect which is produced in the early postoperative period seems to be maintained in the long-term.